Emerging trends in fostering the concept of community among the pentecostal churches in Nigeria (2013)
The establishment of the Pentecostal churches in Nigeria poses many challenges to the Mainline or established Churches such as the Roman Catholic, Anglican, Methodist and Baptist churches, to mention just a few. One of such challenges is the prevalence of the “attitude of belonging” among the Pentecostal movements. In dealing with one another, members of the latter discretely demonstrate unique concern in fulfilling the biblical injunction to be “their brother’s keepers,” a rediscovery of one of the practices in the early church, where communalism was modus operandi. Therefore, this paper aims at exploring this emerging trend in fostering communal life or belongingness in the churches of our study, a reminiscence of communal living in the early church. The paper is not aimed at asserting the total absence of such gesture in the mainline churches, but the dimension of the practice among the Pentecostals which inculcates a sense of belonging in their members, is the concern of this research. In addition, the paper also harped on the fact that, although the concept of belonging is the underlying factor responsible for an astronomical expansion among the Pentecostals today, the factor of communalism generates a negative tendency of exclusion of non-members of the community in the distribution of helpline. Thus, the paper adopts a historical research method as well as fieldwork through oral interviews, library and archival materials.